Analysis of Modernization Readiness of Irrigation in The Downstream Brantas River Basin Under The Authority of The Central Government - Monique Adriana Swandani; Mahendra Andiek Maulana; Yang Ratri Savitri (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2024)
In carrying out the management of the irrigation system has obstacles are inadequate infrastructure conditions caused, the irrigation infrastructure has exhausted its technical age which causes the decline in the performance function of the irrigation network. Government to farmers has not been carried out intensively. In an effort to overcome these obstacles, in addition to the operation, maintenance and rehabilitation required a renewal thoroughly, both institutional, technical, managerial, and human resources. Modernization irrigation is an effort to realize a participant irrigation management system that is oriented toward fulfilling irrigation service levels in an effective, efficient, and sustainable. Limited time, cost and human resources are obstacles in the implementation of irrigation modernization, so an assessment is needed to measure the level of readiness of an irrigation area in carrying out irrigation modernization activities. This result of analyze the readiness of irrigation modernization show that Mrican Kanan area is ready for irrigation modernization with IKMI value 81,69%. Meanwhile DI. Mrican Kiri, DI. Siman, DI. Menturus, DI, Delta Brantas needs maintenance around 1- 2 years. DI. Mrican Kanan can start from the Peterongan Secondary Channel. SI. Pare Peterongan, SI. Tunggorono, SS. Melik dan SS. Sentul.